Decision analysis on cultivation method for shrimp farm in south of garut, cikelet - Prabowo, Arian; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2016)
Abstract. Boedihardjo Shrimp Farm (BSF) established in 2014 as a shrimp farms that cultivate white shrimp prawn types that also called Litopenaeus vannamei that the farm located in southern Garut, Cikelet village. As a group, BSF can be said to be a successful that operated for four cycles. However, production for the four cycles fluctuated quite high.This study tried to find out what the cause of the fluctuations in production that faced by BSF, to look more deeply about matters related to shrimp farming performed by the BSF. The method used in this study is a simple multi-attribute rating technique used to help decision makers select several alternatives. The study of this thesis is the study mode of literature, interviews with competitors, key people in the group, technicians, suppliers and buyers who have worked with BSF that the results will be used for analysis using SMART (simple multi-attribute rating technique). The results of this study are alternatives that will be assessed. Alternative which provides the best value that can later be selected by decision makers as a tool to make decisions for cultivation in Cikelet. By doing so, it is expected to have improvement in the way of cultivation and production results that will be obtained by BSF.Â Key words : Decision making, Shrimp farm, Simple multi attribute rating technique (SMART)